2011
DOI: 10.3390/rs3102263
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Comparison between WorldView-2 and QuickBird-2-Simulated Imagery Regarding Object-Based Urban Land Cover Classification

Abstract: Abstract:The objective of this study is to compare WorldView-2 (WV-2) and QuickBird-2-simulated (QB-2) imagery regarding their potential for object-based urban land cover classification. Optimal segmentation parameters were automatically found for each data set and the obtained results were quantitatively compared and discussed. Four different feature selection algorithms were used in order to verify to which data set the most relevant object-based features belong to. Object-based classifications were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 28 publications
(32 reference statements)
1
54
0
2
Order By: Relevance
“…In the process of hierarchical classification, RF uses a subset of features to build each individual hierarchy, making a more accurate classification decision based on effective features and reducing the error associated with the structural risk of the entire feature vector. Novack et al [54] showed that RF classifier can evaluate each attribute internally; thus, it is less sensitive to the increase of variables (Tables 5 and 6). The object-based classifier can provide faster and better results and can be easily applied to classify forest types [24,39,40,55].…”
Section: Discussionmentioning
confidence: 99%
“…In the process of hierarchical classification, RF uses a subset of features to build each individual hierarchy, making a more accurate classification decision based on effective features and reducing the error associated with the structural risk of the entire feature vector. Novack et al [54] showed that RF classifier can evaluate each attribute internally; thus, it is less sensitive to the increase of variables (Tables 5 and 6). The object-based classifier can provide faster and better results and can be easily applied to classify forest types [24,39,40,55].…”
Section: Discussionmentioning
confidence: 99%
“…[70][71][72][73], and (II) a full primal sketch, equivalent to perceptual grouping [33,52,80], where level 2 boundaries (e.g., texture boundaries) are detected between groups of tokens ( [13]; pp. 53,[91][92][93][94][95]. Unfortunately, Marr provided neither raw nor full primal sketch implementation details.…”
Section: About the Former A Rs-ius Cannot Detect Rs Image-objects Wimentioning
confidence: 99%
“…Unfortunately, image segmentation parameters are always site-specific and must be user-defined based on heuristics and a trial-and-error approach. For example, in the case of the popular Baatz et al segmentation algorithm adopted by the pre-attentive vision first stage of the Definiens GEOBIA/GEOOIA commercial software products [10], statistical methods have been developed to automatically optimize the parameters based on a site-specific training set of reference image-objects [9,85,93].…”
Section: Geobia/geooia Weaknesses (Due To Internal Drivers)mentioning
confidence: 99%
“…As the proposed pre-processing comes in addition and not as a replacement for the suggested procedures in Blaschke et al [12], the aggregation remains valid while integrating the important feature attribute of single pixel objects at the lowest GEOBIA level and using the properties at higher aggregation levels. Urban mapping and single building detection is a common topic in GEOBIA [15], and the use of convolution and edge detection is regarded amongst the more important features in building detection [16]. The equation presented extends the already available list of features where the ability to apply the analysis to very large neighborhoods is related to a trend in the availability of increased hardware capacities.…”
Section: Agricultural Application With Urban Mapping Extensionsmentioning
confidence: 99%